Respuesta :

Answer:

The answer to your question is      f(x) =- [tex]\frac{9}{x}[/tex]  

Step-by-step explanation:

g(x) = 9x - 8

f(x) = ?

h(x) = (f°g)(x) = 9 / (9x - 8)

Process

When we evaluate a function with another function, just substitute the second function in all the x of the first function.

From the information given we notice that g(x) = 9x - 8 and it is in the denominator of the function h(x). This means that before we substitute this value in f(x) there, there was a "x".

Then

          f(x) =- [tex]\frac{9}{x}[/tex]    so   (f°g)(x) =- [tex]\frac{9}{9x - 8}[/tex]   or  h(x) = -[tex]\frac{9}{9x - 8}[/tex]